1993
DOI: 10.1177/000348949310200911
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Paranasal Sinuses in Children: Implications for Paranasal Sinus Surgery

Abstract: The pediatric nasal cavity and paranasal sinuses, when compared to those in adults, differ not only in size but also in proportion. Knowledge of the unique anatomy and pneumatization of children's sinuses is an important prerequisite to understanding the pathogenesis of sinusitis and its complications. It is also important in evaluation of radiographs and in planning surgical interventions. In order to study the development of the paranasal sinuses in children and relate clinical anatomy to sinus surgery, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
1
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 9 publications
(5 reference statements)
10
90
1
6
Order By: Relevance
“…These measures were similar in cadaver skulls (25) . The ethmoidal bulla, however, has not been separately evaluated in theses studies.…”
Section: Anatomical Variantssupporting
confidence: 55%
“…These measures were similar in cadaver skulls (25) . The ethmoidal bulla, however, has not been separately evaluated in theses studies.…”
Section: Anatomical Variantssupporting
confidence: 55%
“…Thus, the results of the present study suggest that the size increase of the maxillary sinus within the primate evolution can't be explained satisfactorily only by the increasing skull size. Notwithstanding that development and growth of the maxillary sinus are closely related to the growth of the skull and to the dentition (Wolf et al, 1993), it has been demonstrated that the sinuses also possess a developmental potential of their own (Libersa et al, 1991;Koppe et al, 1994). On the other hand, recent studies by Francis et al (1990) and Oktay (1992), who have revealed that neither cleft lip and palates nor orthodontic malocclusion affect the size of the maxillary sinus, give some doubts about an exclusive structural role of the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…It develops as evagination of the mucous membrane of the lateral wall of the nasal cavity at the level of the middle nasal meatus forming a minute space that expands primarily in an inferior direction into the primordium of the maxilla Figure 1. The maxillary sinus enlarges variably and greatly by pneumatization until it reaches the adult size by the eruption of the permanent teeth [2]. A significant difference in the bone height of the sinus floor exists between dentulous and edentulous individuals.…”
Section: Introductionmentioning
confidence: 99%